2011
DOI: 10.3945/ajcn.110.006155
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function is impaired after a high-salt meal in healthy subjects

Abstract: An HSM, which reflects the typical amount of salt consumed in a commonly eaten meal, can significantly suppress brachial artery FMD within 30 min. These results suggest that high salt intakes have acute adverse effects on vascular dilatation in the postprandial state. This trial was registered at www.anzctr.org.au/trial_view.aspx?ID=335115 as ACTRN12610000124033.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 32 publications
5
86
3
2
Order By: Relevance
“…Healthy subjects who received a high-salt meal showed impaired endotheliumdependent vasodilation without any blood pressure changes, possibly because of reduced endothelial nitric oxide synthase activity from increased plasma sodium concentrations. 27 Salt intake has also been associated with inflammatory response; brain and serum levels of an inflammatory marker expressed by endothelial cells, E-selectin, are significantly increased in SHR-SPs after salt intake but unchanged in SHRs. 28 Hence, as demonstrated in the effects of salt and hypertension on endothelial dysfunction, VRFs may directly and indirectly cause endothelial dysfunction, and subsequent BBB breakdown can lead to enlarged perivascular spaces, cerebral microbleeds, and WM changes.…”
Section: Pathogenesis Of Cerebral Small Vessel Disease 555mentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy subjects who received a high-salt meal showed impaired endotheliumdependent vasodilation without any blood pressure changes, possibly because of reduced endothelial nitric oxide synthase activity from increased plasma sodium concentrations. 27 Salt intake has also been associated with inflammatory response; brain and serum levels of an inflammatory marker expressed by endothelial cells, E-selectin, are significantly increased in SHR-SPs after salt intake but unchanged in SHRs. 28 Hence, as demonstrated in the effects of salt and hypertension on endothelial dysfunction, VRFs may directly and indirectly cause endothelial dysfunction, and subsequent BBB breakdown can lead to enlarged perivascular spaces, cerebral microbleeds, and WM changes.…”
Section: Pathogenesis Of Cerebral Small Vessel Disease 555mentioning
confidence: 99%
“…В нескольких других исследованиях по изучению вли-яния пищевой соли на организм человека показали не только ее косвенное (гипертензионно-опосредованное), но и прямое воздействие на эндотелий. У здоровых лиц, получавших большое количество соли, выявили наруше-ние эндотелий-зависимой вазодилатации без каких-либо изменений уровня артериального давления, возможно, из-за снижения активности эндотелиальной синтазы оксида азота в связи с повышением концентрации натрия в плазме крови [27]. Потребление соли также было ассо-циировано с воспалительной реакцией; у КСГПИ после употребления соли отметили значительное повышение содержания Е-селектина, воспалительного маркера, экс-прессируемого эндотелием, в головном мозге и сыворот-ке крови; однако у КСГ таких изменений не было [28].…”
Section: патологический каскад бмцс: роль артериальной гипертензии и unclassified
“…March 11, 2014 of overall coronary vasodilator capacity and microvascular function. 36 High sodium intake has been positively associated with endothelial dysfunction, 37,38 resistance to the protective effects of renin-angiotensin-aldosterone system blockade (independent of blood pressure), 39,40 and increased left ventricular mass. 41 Conversely, sodium reduction has been shown to decrease left ventricular mass, 42 to improve pulse wave velocity, 43 and to reduce albuminuria in normotensive 44 and hypertensive subjects, 45 independent of blood pressure.…”
Section: Figurementioning
confidence: 99%
“…46) Regarding vascular damage, it has been shown that high dietary salt decreases plasma nitrate and nitrite and impairs endothelial function in humans. 47,48) The salt-induced endothelial dysfunction and damage may promote structural changes in arteries and kidney disease. 49) High sodium intake has been associated with increased carotid intima-media thickness in obese subjects, and with central pulse pressure and augmentation index in hypertensive patients.…”
Section: Salt and Organ Damagementioning
confidence: 99%